INTERACTIVE TECHNOLOGIES IN TRAINING FUTURE SPEECH THERAPISTS - Melnychuk, Iryna (Mountain School of Ukrainian Carpaty, 2019)
It has been generalized in the article that vocational training of future speech therapists is based on mastering by students abilities in adjusting some components of impaired speech activity, which manifest themselves in the early stages of the child’s development. The use of interactive technologies in training future therapists, who are called to master the abilities and skills in organization of optimal interpersonal interaction with children that have speech disorders, has been actualized. The purpose of research is to reveal the possibilities of interactive technologies in training future speech therapists to work by specialty and ground the methods of using interactive exercises in speech therapists’ work. It has been established that for correctional and developmental work with children with severe speech disorders specialists, speech therapists can use interactive tasks. In the process of vocational training future speech therapists must try such interactive exercises, which they could use at the classes for children with speech disorders. Such tasks include exercises for articulatory gymnastics. The article provides examples of some interactions for teaching future speech therapists to work with children that have speech disorders. It has been proved that in vocational training of future speech therapists is necessary to orient students at elaboration of individual strategy of correcting speech disorders in the development of every child. With this purpose it is advisable to try some interactive exercises first, which future specialists can adapt for purposeful development of speech activity of a separate child, who has individual specific speech disorders, related to mental and physical changes in organism, problems with health that complicate social adaptation, study, development of children. Thus, using interactive technologies in the process of vocational training future speech therapists aims to solve several important and interrelated tasks: direction of vocational education at a real practical activity of speech therapist that will promote growing the level of its competitiveness in the modern labor market; formation of abilities in using personally oriented approach to children with various speech problems; development of creativity in the creating individual strategies for organizing interactive interaction with children with speech disorders by adapting the exercises and technologies tested during study process.